The development of online car care reservation system - Pakdeetrakulwong, Udsanee (Journal of Science and Technology Songkhla Rajabhat University, 2022)
Car care service shop provides services related to car cleaning and maintenance. There are several services including oil changing, tire pressure checking, other vehicle maintenances, washing, vacuuming, polishing, painting, class coating, polishing and stain removal. Customers must bring their cars to the service center; however, in case that they are not convenient to come to the place, some centers will also provide off-site services. Customer who want to receive the service must call in advance to book an appointment. Nowadays, the form of booking a reservation is mostly done via phone. The main problem arising is regarding distant communication error. In addition, it takes a long time to explain the form of car care services and various promotion to a new customer. This research aims to develop a web application system for self-service reservation to support customers to view car care service information about services, expenses, promotional information. In addition, the developed system also facilitates car care service centers to manage reservation information in digital format in order to build summary reports, as well as for further analysis in the future.